2009
DOI: 10.1136/bmj.b1344
|View full text |Cite|
|
Sign up to set email alerts
|

Four layer bandage compared with short stretch bandage for venous leg ulcers: systematic review and meta-analysis of randomised controlled trials with data from individual patients

Abstract: Objective To compare the effectiveness of two types of compression treatment (four layer bandage and short stretch bandage) in people with venous leg ulceration.Design Systematic review and meta-analysis of patient level data. Data sources Electronic databases (the Cochrane CentralRegister of Controlled Trials, the Cochrane Wounds Group Specialised Register, Medline, Embase, CINAHL, and National Research Register) and reference lists of retrieved articles searched to identify relevant trials and primary invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
102
0
13

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(117 citation statements)
references
References 19 publications
2
102
0
13
Order By: Relevance
“…51 A meta-analysis of RCTs with pooling of individual patient data from five trials comparing 4LB with short stretch bandage found that the 4LB was associated with a significantly shorter time to healing. 53 The VenUS study, found that 4LB was less expensive than non-cohesive SSB which required more re-applications and changes of dressings. However, the SSB could have been reused or replaced by cohesive SSB which can stay in place for up to a week and the cost of nurse training in 4LB was not considered.…”
Section: Multicomponent Systems Incorporating Elastic Bandage (4lb) Vmentioning
confidence: 99%
See 1 more Smart Citation
“…51 A meta-analysis of RCTs with pooling of individual patient data from five trials comparing 4LB with short stretch bandage found that the 4LB was associated with a significantly shorter time to healing. 53 The VenUS study, found that 4LB was less expensive than non-cohesive SSB which required more re-applications and changes of dressings. However, the SSB could have been reused or replaced by cohesive SSB which can stay in place for up to a week and the cost of nurse training in 4LB was not considered.…”
Section: Multicomponent Systems Incorporating Elastic Bandage (4lb) Vmentioning
confidence: 99%
“…In a Cochrane review, most of the trials comparing single layer systems with multicomponent systems were small and underpowered. 53 A single large RCT (n=245) suggested a benefit for four layer bandage (4LB) when compared with elastic adhesive single component compression. 54 One trial compared two components with four components and found a statistically significant difference in frequency of complete healing in favour of the 4LB at six months.…”
Section: Multicomponent High Compression Versus Single or Two Componementioning
confidence: 99%
“…Many of the important data requirements for venous leg ulcer research have already been established from prognostic research, experience with large RCTs and an existing example of IPD meta-analysis in wound management. 18,19,187,225,226 For example, larger ulcer area and longer ulcer duration at the outset of treatment are known to be independent and significant predictors of delayed healing. 225,226 In terms of outcome assessment, time to healing is considered as much more informative than frequency of complete healing at fixed time points or intermediate healing measures because it provides information not only on whether or not healing occurs but also on how long it takes to occur.…”
Section: Exploration Of Potential Data Required For Individual Patienmentioning
confidence: 99%
“…In this case, an earlier Cochrane review had not shown a difference in healing between the two bandages when trial-level data were pooled, 184 whereas a subsequent IPD meta-analysis of the same comparison, involving estimation from an adjusted Cox proportional hazards model, showed that, on average, patients healed faster with the four-layer bandage. 187 The main issue with undertaking IPD meta-analysis is that the success of the endeavour is contingent on the review team being able to access the original data for each eligible primary study, although IPD meta-analysis may still be beneficial even if data can be obtained for only a subset of eligible studies. Access to the original patient-level data may not always be straightforward; for example, data may no longer be available for older studies.…”
Section: Introductionmentioning
confidence: 99%
“…5a, b). 126 O'Brien et al obtained a 54% healing rate at 3 months in patients using a four layer compression system, in comparison to 34% healed in a control group receiving 'usual care', where only 5 of 100 participants received some type of compression. 127 In a standing individual, the venous pressure, which equals the weight of the blood column between the foot and right atrium, is about 80-100 mm Hg.…”
Section: Translations/interventionsmentioning
confidence: 99%